Kadar Sianida Singkong Rebus dan Singkong Goreng - Yeni Purwati; Anny Thuraidah; Dinna Rakhmina (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2016)
Cassava is the third staple food often used by people to make a variety of products. Carbohydrates from cassava also contains toxic compound such as cyanide which can inhibit the action of respiratory enzymes. Cyanide in cassava can be removed by boiling or frying process. The aim of research was to find out the cyanide level differences between boiled cassava and fried cassava. This type of research was experiment, with design of comparative studies approach. Cyanide levels were examined in 10 samples with 2 treatments using Argentometry Volhard titration method. The result showed the average of cyanide levels in boiled cassava was 0.772 ppm and in fried cassava was 1.069 ppm. The percentage of cyanide levels reduction in boiled cassava was 28,78%, while for the fried cassava was 0%. The statistical test obtained the value of p